Fatty acid composition differs between emergent aquatic and terrestrial insects—A detailed single system approach - Parmar, Tarn Preet; Kindinger, Alina L.; Mathieu-Resuge, Margaux; Twining, Cornelia W.; Shipley, Jeremy Ryan; Kainz, Martin J.; Martin-Creuzburg, Dominik (Frontiers in Ecology and Evolution, 2022)
Emergent insects represent a key vector through which aquatic nutrients are transferred to adjacent terrestrial food webs. Aquatic fluxes of polyunsaturated fatty acids (PUFA) from emergent insects are particularly important subsidies for terrestrial ecosystems due to high PUFA contents in several aquatic insect taxa and their physiological importance for riparian predators. While recent meta-analyses have shown the general dichotomy in fatty acid profiles between aquatic and terrestrial ecosystems, differences in fatty acid profiles between aquatic and terrestrial insects have been insufficiently explored. We examined the differences in fatty acid profiles between aquatic and terrestrial insects at a single aquatic-terrestrial interface over an entire growing season to assess the strength and temporal consistency of the dichotomy in fatty acid profiles. Non-metric multidimensional scaling clearly separated aquatic and terrestrial insects based on their fatty acid profiles regardless of season. Aquatic insects were characterized by high proportions of long-chain PUFA, such as eicosapentaenoic acid (20:5n-3), arachidonic acid (20:4n-6), and α-linolenic acid (18:3n-3); whereas terrestrial insects were characterized by high proportions of linoleic acid (18:2n-6). Our results provide detailed information on fatty acid profiles of a diversity of aquatic and terrestrial insect taxa and demonstrate that the fundamental differences in fatty acid content between aquatic and terrestrial insects persist throughout the season. However, the higher fatty acid dissimilarity between aquatic and terrestrial insects in spring and early summer emphasizes the importance of aquatic emergence as essential subsidies for riparian predators especially during the breading season.